Warunki organizowania pracy w zespole - Реnс, Józef (Wydział Prawa i Administracji UAM, 1989)
In search of higher productivity of work more attention should be paid to organization of work, which in our country is still very neglected. Its improvement is the cheapest and at the same time efficient way of attaining the growth of productivity. Nowadays, work should be organized so as to stimulate active and enterprising behaviours, to make it possible to utilize growing skills of employees and to encourage their cooperation and strive to success. The above requirements are to a considerable degree met by team forms of organization of work, used in many countries to achieve higher productivity and quality of work and quality of life at a workplace. Team forms of organization of work strengthen ties between people and create better conditions of their cooperation, based on the strive of individuals to achieve a comon aim and on their integration with the aims and activity of their enterprise. The countries which use the above method, especially capitalistic countries, treat it as an important source of growth of productivity, initiative and invention of employees and the source of their satisfaction from work. Considerable experience as well as significant economic and humanistic effects result from the use of that method in the USSR. In Poland, its application is in the stage of experiments; thus our experience is very limited and our results have little diagnostic value. Organizing team work requires that certain conditions be met. In particular, it is necessary to determine the size and composition of a team, to determine the scope and evaluation of its work, to work out just methods of distribution of remuneration, to verify the system of norms applicable in an enterprise, to organize the cost evaluation system, to define the rules of cooperation, and to improve the supply system. A failure to meet such conditions would distort the idea of team work and would increase the employees' reluctance to implement it.
Conditions of organizing team work